A New Domino Reaction under Microwave Irradiation for the Synthesis of Pyrazolo[5,1- b ]quinazolinones - Ng, Jia Hui; Lim, Felicia Phei Lin; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Thieme, 2023)
Pyrazolo[5,1-b]quinazolinones were synthesized by consecutive pyrazole and quinazolinone ring closures in a new catalyst-free microwave-promoted domino reaction of hydrazine with 2-cyano-3-(methylthio)-3-(2-methoxycarbonylphenylamino)acrylates, which were prepared from methyl anthranilate and 2-cyano-3,3-bis(methylthio)acrylates. When 2-cyano-3,3-bis(methylthio)acrylates reacted directly with anthranilic acid hydrazide, the arylamino group remained intact, while the hydrazide moiety transformed into 1-acylpyrazoles and further to 2-(1,3,4-oxadiazolylidene)-2-cyanoacetates. The structures of representatives from each group of the prepared heterocyclic compounds were examined in detail by X-ray crystallography.